Eksternalitas Terhadap Konversi Mangrove Menjadi Tambak Garam di Desa Bipolo Kecamatan Sulamu, Kabupaten Kupang, Nusa Tenggara Timur - Amheka, Jusuf Ariyanto; Dethan, Fouren YE (Neolectura, 2024)
The utilization of mangrove forest land for the expansion of salt pond areas with the aim of increasing salt production in Bipolo Village causes the loss of economic value of marine biota in the mangrove ecosystem. Mangrove ecosystem resources that are utilized as salt ponds if not accompanied by a rehabilitation process will cause a decrease in the function of the mangrove ecosystem. This will later become a challenge as well as create externalities that need attention from the Kupang district government in regulating the utilization of the mangrove ecosystem in Bipolo Village. This study aims to analyze the positive and negative externality values ??resulting from the development of salt pond businesses in Bipolo Village, Sulamu District, Kupang Regency. To determine the positive and negative externality values ??using the economic valuation method. Based on the results of the study, it is known that the salt pond business in Bipolo Village provides a negative externality value of Rp. 21,439,466,084 and a positive externality value of Rp. 235,280,000 which means that the opening of salt pond land has caused losses from the ecological side of the mangrove which is quite large compared to the benefits obtained.